2013
DOI: 10.1002/cncy.21354
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of a positive axillary lymph node fine‐needle aspirate in patients with invasive breast carcinoma

Abstract: BACKGROUND: Image-guided axillary lymph node fine-needle aspirates (FNAs) correlate well with pathologic lymph node staging in cases of invasive breast carcinoma. The objective of this study was to determine the prognostic significance of a positive lymph node. METHODS: Consecutive cases of nonmetastatic (M0) invasive breast carcinoma evaluated by image-guided FNA were identified (4-year period, median follow-up of 51 months). "Positive" and "nonpositive" groups were compared using Kaplan-Meier survival analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Axillary lymph node metastasis in primary breast cancers has long been used clinically as a poor prognostic indicator [37] but there remains controversy about whether axillary lymph node metastasis reflects lead-time bias or true tumor biology (that is, metastatic potential or aggressiveness) [37-39]. Multivariate analysis of our combined expression array datasets did not reveal lymph node status to be prognostic for PFS although we found that RIP2 mRNA expression correlated with extensive axillary lymph node invasion in stage-III breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Axillary lymph node metastasis in primary breast cancers has long been used clinically as a poor prognostic indicator [37] but there remains controversy about whether axillary lymph node metastasis reflects lead-time bias or true tumor biology (that is, metastatic potential or aggressiveness) [37-39]. Multivariate analysis of our combined expression array datasets did not reveal lymph node status to be prognostic for PFS although we found that RIP2 mRNA expression correlated with extensive axillary lymph node invasion in stage-III breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…267 This is facilitated by placing the samples in a cell-preservation medium and, after retrieving the tissue fragments for formalin fixation, using the fluid medium for flow cytometry. 267 Lymph node FNAB for cytology can be used as an independent prognostic indicator for metastatic breast cancer, 268 as can the presence of CYFRA 21 keratin biomarker. 269 Fine-needle aspiration biopsy of lymph node can also be used in allergy studies to assess effectively the complex immune reaction following intradermal antigen challenge.…”
Section: Lymph Nodementioning
confidence: 99%
“…They showed that cases with positive axillary FNA have more advanced disease with poorer prognosis and more aggressive treatment. They concluded that axillary FNA could be used as a preoperative staging procedure [21]. …”
Section: Breastmentioning
confidence: 99%